Influência da hipermobilidade articular generalizada sobre as funções estomatognáticas, articulação temporomandibular e oclusão dentária - Chiodelli, Lais (2014)
Generalized joint hypermobility (GJH) is an extreme variation of normal joint mobility and it is considered a benign and non- pathological phenomenon. Among its manifestations are the reduction of the proprioception and, consequently, of the motor coordination. It is believed that the temporomandibular joint (TMJ) is amongst the joints affected by GJH . This fact instigated this research, which propose to evaluate the influence of GJH on the TMJ, the stomatognathic functions of mastication and deglutition, and dental occlusion in women. Forty three women participated, voluntarily, in the study conducted at the Speech-Language-Hearing Service of UFSM. The HAG was assessed according to the criteria of Carter and Wilkinson, modified by Beighton and, based on the scores obtained in this scale, the volunteers were distributed into two groups: with GJH (GH, n=17) and without GJH (GSH, n=26). The signs of TMD were examined according the instrument Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD); mastication and deglutition were assessed through myofunctional orofacial exam (MBGR protocol Marchesan, Berretin-Felix, Genaro, Rehder, 2009); and the occlusion evaluation comprised: the Angle Class, presence of overbite, overjet, openbite or crossbite, pattern of desocclusion and occlusal interference. The analyzed results showed prevalence of clicks during jaw movements (52.9%) and mouth opening deviation (76.5%) in the GH. The mastication pattern appeared abnormal in 48,1% of volunteers of GH, and there was a significant association between the mastication pattern and the mouth opening pattern, only in the GSH (p=0.05). Regarding occlusion, no volunteer had an ideal occlusion and there was no significant difference between the groups in the Angle Class. Higher percentage of changes in the occlusion was observed in the GH (29.4 % of overbite, 47.1% of overjet and 17.6% of crossbite), with statistically difference of crossbite in the GH (p=0.05). These findings suggest that women with GJH have a reduction of the proprioception and, consequent impairment of the joint stability and the neuromuscular coordination. Moreover, the occlusal changes in women with GJH may be resulting from the connective tissue fragility present in this condition.